Influence of Processing Conditions on Mechanical Behaviours of Thermoplastic Natural Rubber/ Polyaniline Blend / Farrah Diyana Zailan...[et al.] - Zailan, Farrah Diyana; Ruey, Shan Chen; Ahmad, Sahrim; Shahdan, Dalila; Baharin, Khairunnisa Waznah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
The blend fabrication of thermoplastic natural rubber (TPNR) and polyaniline (PANI) was carried out to determine the optimization of processing conditions by the mechanical testing (tensile, bending and Izod impact test). The TPNR matrix, made up of linear low-density polyethylene (LLDPE), natural rubber (NR), and liquid natural rubber (LNR) as compatibilizer with the composition ratio at 40:50:10. TPNR/PANI (90 wt % / 10 wt %) blends was prepared via a melt blending method using an internal mixer with various processing parameter conditions. The influence of processing conditions including the processing temperature (°C), speed of rotation (rpm) and processing time (min) on the mechanical properties of blend were investigated. The results showed that the optimum processing conditions for preparing the TPNR/PANI blend was obtained at 130 °C, 30 rpm and 13 min. The morphological test has been done on TPNR, and TPNR/PANI blends using SEM characterization. The SEM micrographs confirmed the good dispersion of PANI within TPNR matrix.